The Application of Composter Reactor Technology Using The Anaerobic Fermentation Method for Processing Organic Waste at a Residential Scale - Lelono, Asmoro; Alfiyani, Nur Asyia; Intani, Rini Nur; Dewi, Rosita Fitrah; Sari , Dwi Rihma (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Community-based waste management is a program designed to empower citizens, who are the primary producers of household waste, to take responsibility for ensuring that the waste they generate is sorted and utilized as efficiently as possible before disposal. This initiative aims to empower residents to manage organic waste by applying composter reactor technology through anaerobic fermentation methods within residential areas. To implement this program, we have partnered with the BSU ASRI BMP Waste Bank Unit, which has been active since 2021 and possesses experience and expertise in waste management. The activity began with planning, followed by a series of steps including socialization, demonstrations, the creation, and distribution of composters. The program concluded with an evaluation to assess the sustainability and effectiveness of the activities carried out. The results show that the application of composter reactor technology on the dasa wisma community has successfully transformed household waste into compost and liquid organic fertilizer. These products have been used as planting media and fertilizers for ornamental and horticultural plants at home gardens. Additionally, the use of decomposers has significantly reduced the volume of organic waste previously discarded by converting it into valuable products.